Pengetahuan Suku Muna Tentang Kameko di Desa Kabangka Kecamatan Kabangka Kabupaten Muna - Asriani, Asriani; Winesty Sofiani, Wa Ode; Rahman, Abdul (JURNAL KABANTI: Kerabat Antropologi, 2024)
This research was conducted to find out how the knowledge of the Muna tribe on kameko in Kabangka Village, Kabangka District, Muna Regency and how the utilization of kameko in the Muna tribe in Kabangka Village, Kabangka District, Muna Regency. The methods used in this research are purposive sampling for the selection of informants, interview and observation methods for the data collection process in the field, and qualitative descriptive methods for examining information by utilizing point-by-point depiction of research results to answer the problems considered. The results concluded that Kameko is one of the traditional drinks originating from Southeast Sulawesi Province which is usually served in every traditional cultural ritual that still exists today. Kameko, which is made from fermented nira and mangrove wood, can contain alcohol. Talking about kameko drinks in Kabangka Village, there are many komeko which are used as their daily livelihoods such as, in terms of public knowledge on kameko, one of which is in terms of tapping, maintaining kameko and fermentation, the second is public knowledge in the utilization of kameko such as kameko can be used as a traditional drink of arak type, as brown sugar, health, people in Kabangka Village in utilizing kameko still use simple traditional tools.